Curahan Waktu Kerja Petani Penggarap Pada Usahatani Padi Sawah Di Kelurahan Woloan Dua Kecamatan Tomohon Barat - Tirukan, Joey Bryllio; Sendow, Martha Mareyke; Timban, Jean Fanny Junita (Sam Ratulangi University, 2023)
The aim of the study was to determine the working time of farmers working on lowland rice farming in Woloan Dua Village, West Tomohon District. This research was carried out from May to July 2023. The data used in this research are primary data and secondary data. Primary data was obtained through direct interviews with rice farming cultivators, using a list of questions that had been prepared in the form of a questionnaire. While secondary data were obtained from official sources, namely the Woloan Dua Village office, as well as other sources related to this research. The sampling method was carried out by purposive sampling, namely samples taken deliberately. The results showed that the working time of sharecroppers on lowland rice farming in Woloan Dua Village, West Tomohon District was 3072 hours. What is spent on lowland rice farming activities is land preparation, seeding, planting, fertilizing, pest and disease prevention, driving away birds, harvesting, threshing, transportation. And in a day it takes 8 hours, a week it takes 48 hours, a month it takes 192 hours, and per planting period it takes 3072 hours.